Adsorption of Hexavalent Chromium from Wastewater Utilizing Chitosan Based Activated Carbon Prepared from Butea monosperma Bark - Hunge, S. S. (Science and Technology - Recent Updates and Future Prospects Vol. 1, 2024)
The present study highlights about adsorption of Hexavalent Chromium from Wastewater Utilizing Chitosan Based Activated Carbon Prepared from Butea monosperma Bark. Waste water from many industrial operations contains hexavalent chromium metal ions, which worsen environmental degradation. The literature contains documentation of common physical and chemical treatment methods for getting rid of hexavalent chromium. Not only are these methods costly and energy-intensive, but they also seem to produce a build-up of potentially dangerous byproducts. The current study used chitosan-coated Butea monosperma bark-activated carbon to extract hexavalent chromium from an aqueous solution. The batch experiment was used to investigate the pH effect, time of contact with the adsorbent, adsorbent dose, and the starting concentration of Cr (VI) ions. The pH of the biosorbent was found to be optimum at three for Cr (VI) sorption. The elimination of Cr(VI) from the solution will be accelerated with the rise of contact time. Up to 94% more Cr (VI) can be extracted for every unit increase in adsorbent dose. As the blood level of Cr (VI) increased, so did the clearance rate. In this study, researchers discovered that a pre-treated biosorbent was an excellent material for eliminating Cr(VI) ions from contaminated water. The final results revealed up to a 73% reduction in percentage elimination of Cr(VI). Adsorbents have confined a wide variety of active sites to saturate at a certain concentration, which justifies this result.